Analytical Study of Lung Cancer: Risk Factors and Clinical Characteristics - خوري, دنيا; الخير, محمد; عيسى, رنا (Latakia University Journal -Medical Sciences Series, 2025)
Background: Lung cancer is the most common cancer and the leading cause of cancer-related deaths as of 2022. It is expected to remain a significant health issue in the first half of this century, with the increasing incidence and mortality rates. The characteristics of lung cancer vary by geographical region, necessitating a comprehensive analytical study that includes risk factors, clinical, radiological, and histopathological features specific to our country. Methods: The study sample comprised 183 patients who presented with clinical or radiological suspicion of lung cancer, confirmed through histopathological examination. A detailed medical and personal history was collected, including age, habits, residence, occupation, body mass index (BMI) and personal and family medical history, alongside recording radiological and histopathological findings and disease staging. Results: Males constituted the vast majority of the study population (79.2%), with the largest proportion of patients (55.2%) being over 60 years old. The prevalence of current or former smokers was noted at 91.8%. Additionally, 53% of patients were from rural areas, and 54.6% had a normal weight. A history of respiratory diseases was present in 20.2%, predominantly chronic obstructive pulmonary disease (COPD) at 78.4%, which correlated with an increased risk for squamous cell carcinoma. A family history of cancer was noted in 8.2% of cases. Cough was the most common clinical symptom (64.5%), and a higher incidence was observed in the upper lobes (43.7%). The most prevalent histological type was squamous cell carcinoma (34.4%), while adenocarcinoma was more common among females and non-smokers. Most patients were diagnosed at an advanced stage, with distant metastases found in 42.6%, primarily affecting the liver (35.9%). Conclusion: This study highlights the significant risk factors associated with lung cancer in our population, emphasizing the predominance of male patients, high smoking rates, and advanced disease at diagnosis. The findings underline the need for targeted prevention strategies and early detection programs to mitigate the burden of lung cancer in our region.